Collaborative Entrepreneurship sebagai Strategi Pt. X dalam Menghadapi Krisis di Masa Pandemi Covid-19 - Annisa Merniawanda; Noviaty Kresna Darmasetiawan (Syntax Literate, 2023)
X has three services, namely pest control, garden maintenance, and general trade. During the COVID-19 pandemic, only the general trade service operated normally. PT. X identified an opportunity due to the increased demand for health and hygiene support equipment as a result of the COVID-19 pandemic. However, when PT. X obtained a project for the procurement of hand sanitizers and handwashing soap, they realized that they were not fully capable of handling the project entirely due to resource constraints. PT. X decided to collaborate with a partner company that had expertise and experience in the production of health support equipment. The research aims to identify the reasons why PT. X turned to collaborative entrepreneurship, how to operate collaborative entrepreneurship, and the role and implementation of social capital theory in building trust in the process of creating collaborative entrepreneurship as a strategy to overcome the crisis caused by the COVID-19 pandemic. The research uses a qualitative method with primary data obtained from interviews with informants from PT. X and secondary data obtained by observing the situation faced by PT. X. The results of this study indicate that PT. X successfully survived this COVID-19 pandemic. This research is expected to provide insights into the collaborative strategies adopted by PT. X in overcoming the crisis caused by the COVID-19 pandemic, as well as the application of social capital theory in building trust in cooperation with business partners.